Manipulation of vehicle scales in legal metrology - Asmazatul Adawiyah Ramley; Mohamad Rizal Abd Rahman; Zarina Shukur; Muhammad Azwan Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2025)
To ensure Malaysia’s economic growth aligns with modern technologies, a focused approach to legal metrology is essential, particularly regarding the manipulation of vehicle scales. This study aims to identify effective metrological legal controls to address the manipulation and modification of vehicle weighing devices prevalent in contemporary business transactions. It also analyzes the effectiveness of these legal controls in detecting and preventing such malpractices. Using a qualitative approach, including legal analysis, document reviews, and stakeholder interviews, the study identifies gaps in Malaysia’s legal metrology system, highlighting that outdated legislation and inadequate software verification megsures enable traders to tamper with computerized weighing systems. Enforcement challenges further exacerbate these issues, as current inspection protocols often overlook digital manipulations. To address this, legal metrology must evolve by incorporating advanced software verification, updating the Weights and Measures Act 1972, and enhancing inspector training. Strengthening regulatory frameworks and enforcement mechanisms will reinforce compliance and accountability, ultimately protecting consumers and ensuring fair trade practices. Addressing manipulation within legal metrology is crucial for fostering a transparent trading environment that supports sustainable economic growth and enhances the integrity of vehicle scales in Malaysia’s trade ecosystem.